Connecting the Dots: A Theoretical Review of Human Resource Practices, Employee Engagement, and Service Delivery in Local Municipalities of Mpumalanga, South Africa - Mkhabela, LZ.; Isabirye, AK. (Journal of Ecohumanism, 2025)
Local municipalities in Mpumalanga Province, South Africa, face the challenge of meeting increasing service delivery demands while navigating a dynamic operational environment. This research reviews the critical connection between human resource (HR) practices, employee engagement, and effective service delivery within the local government sphere in the province. The research employs qualitative methods of a literature review genre. Scholarly literature was obtained from search engines like Google Scholar, JSTOR, EBSCOhost, from Statistics South Africa reports, the Auditor-General and Department of Cooperative Governance and Traditional Affairs (COGTA). The research used specific search terms including worker empowerment, employee engagement, recruiting, HR management and capacity building to find relevant scholarly and context-specific sources. Results show that HR practices in Mpumalanga municipalities are mainly fragmented and reactive, leading to erratic employee engagement and diminishing organizational efficiency. The research highlights the need for a strategic restructuring of HR processes, proposing a combination of employee engagement into the development of organizational goals. It recommends well-structured job descriptions harmonized with municipal requirements, multi-channel recruitment strategies, and systematized selection guidelines. Additionally, the study underscores the need for thorough engagement frameworks integrating fair compensation, performance management connected to strategic objectives, and employee wellness initiatives. The review deduces that proactive, strategically coordinated HR practices are necessary for enhancing continuous employee engagement and, eventually, augmenting the quality and consistency of public service delivery within Mpumalanga's local municipalities.